Pengaruh model pembelajaran problem based learning dengan menggunakan powerpoint terhadap hasil dan minat belajar siswa pada materi laju reaksi di kelas XI SMA - Saragi, Lisken; Makharany Dalimunthe (Educenter : Jurnal Ilmiah Pendidikan, 2022)
This study aims to determine the learning outcomes of students who are taught using a problem based learning model using powerpoint are higher than the learning outcomes of students who are taught conventionally. This research was carried out at SMA Negeri 1 Lawe Sigala-gala, Aceh Tenggara in December 2021. From the results of the study, the results of the study in the experimental class wereobtained with an average pretest score of 25.29 and for the posttest in the experimental class, the average score was 80, 88. While the control class obtained an average value of 24.41 and for the posttest control class obtained an average value of 74.12. Students' learning interest before being given treatment in the experimental class obtained an average value of 69.59, for the control class the average value was 65.00. After being treated in the experimental class, the average value was 80.00 and in the control class, the average value was 70.76. The normalized N-Gain value for students in the experimental class is higher than the value in the control class, namely 0.6842> 0.6315 or the percentage of N-Gain in the experimental class is 68% and the control class is 63%. And for the N Gain value of student interest in the experimental class is higher than the value in the control class, namely 11.111> 0.0625 or the percentage of N-Gain in the experimental class is 11% and the control class is 6.25%.